Impact of Tourism in the Local Economy of Sauraha - Dongol, Prabin (Nepal Tourism and Development Review, 2013)
This study explores the aspects of Chitwan as a tourist destination. The discussion is based on a field work in Chitwan National Park (CNP), Sauraha. DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7384 Nepal Tourism and Development Review Vol.2(1) 2012 148-154